2023
DOI: 10.1111/ijlh.14165
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastometry and prediction of in‐hospital mortality in neonates with sepsis

Rozeta Sokou,
Andreas G. Tsantes,
Maria Lampridou
et al.

Abstract: IntroductionThis study aimed at evaluating the role of rotational thromboelastometry (ROTEM) assays in the prediction of in‐hospital mortality of neonates with sepsis.MethodsOver a 6‐year period, 129 neonates with confirmed sepsis, hospitalized in our neonatal intensive care unit (NICU) were included in the study. Demographics, clinical, and laboratory data were recorded at the sepsis onset and ROTEM assays were performed. Modified neonatal multiple organ dysfunction (NEOMOD) and neonatal sequential organ fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, perhaps because of the historical difficulty in interpretation in neonates ( 32 ), D-Dimer is neither a test routinely conducted on the NICU population nor sufficiently measured in this cohort to facilitate meaningful study (51 D-dimer measures in 22 patients among 339 coagulation tests studied). Rotational thromboelastometry, which evaluates phases of the clotting process, showed utility to identify those at the highest risk of mortality when routinely sent among a cohort of neonates with sepsis ( 33 ). As developmental normative values are being characterized, this testing may represent an additional or alternative way to measure the effectiveness of clotting in neonates with sepsis ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, perhaps because of the historical difficulty in interpretation in neonates ( 32 ), D-Dimer is neither a test routinely conducted on the NICU population nor sufficiently measured in this cohort to facilitate meaningful study (51 D-dimer measures in 22 patients among 339 coagulation tests studied). Rotational thromboelastometry, which evaluates phases of the clotting process, showed utility to identify those at the highest risk of mortality when routinely sent among a cohort of neonates with sepsis ( 33 ). As developmental normative values are being characterized, this testing may represent an additional or alternative way to measure the effectiveness of clotting in neonates with sepsis ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of ROTEM parameters to assess disease severity in neonates has also been reported in previous studies. [68][69][70] Increased creatinine levels emerged as a prognostic factor for hemorrhage in critically ill neonates; however, it is unclear whether this relationship is causal or a result of confounding factors owing to disease severity. Studies in adults with renal insufficiency have demonstrated complex interactions between uremic toxins, vascular wall and coagulation factors, and platelets.…”
Section: Discussionmentioning
confidence: 99%